Information Management for the Fate of the Limitation of Liability Clauses After the Termination of the Contract in French Law - Mallet, Pierre; Flayyih, Najlaa T (ExcelingTech, 2020)
The termination of a contract for non-performance does not preclude the application of the limitation of liability clause that was provided for in the contract. This clause therefore survives the retroactive annihilation of the contract following resolution. However, the scope of such a solution must be carefully considered. After the two rulings of the Cour de cassation (French Supreme Court) that ruled on the survival of limitation of liability clauses, the first of October 5, 2010, handed down specifically on the subject of a limitation of liability clause, and the second of May 3, 2012, which concerned all “contractual stipulations governing the conditions and consequences of its unilateral termination”, the Commercial Chamber of the Cour de cassation revived the plot by restoring, in a ruling of February 7, 2018, the full effectiveness of the limitation of liability clause in the event of termination of the contract for non-performance. There is no doubt that the letter of the new article 1230 of the Civil Code, resulting from the order of February 10, 2016, will have guided the spirit of the advisers. Henceforth - says the law- “the resolution does not affect either the clauses relating to the settlement of disputes, or those intended to take effect even in the event of resolution”. So in both the old and new contract law, limitation of liability clauses have a bright future ahead of them